Effect of Printing Pressure to Paving Block with 5% Weight of Added Fly Ash on Compressive Strength - Nurzal Nurzal; Edison Edison; Krisna Krisna (Jurnal Teknik Mesin (JTM), 2016)
This research aims to investigate the effect of compacting pressure variations with the addition of 5 wt.% fly ash (Fa) on paving block (Pb) in the compressive strength test base on SNI 03-0691-1996. Fa is obtain from waste material produced from coal burning thermal power plant from Sijantang sawahlunto. The growing production of  Fa caused negative environmental impact, so that one of the solutions to overcome that effects is to use the Fa as a raw material for paving block mixture that can reduce the cost of raw material and increase its strength.The fly ash composition in the paving blocks manufacture, that is: 0 wt.%,   5wt.% Fa + block paving material (cement and sand), pressure variation 55, 65, 75, 85 and 95 Kg/cm2 with a drying time for 35 days. The addition of 5 wt.% Fa in paving block is taken based on the results of research conducted in 2013 by using a variation of the composition of 0,5,10,15 wt.% Fa and obtained optimum conditions at 5 wt.% Fa, while the optimal time drying 35 days is taken based on the results of research conducted in 2014 by the drying time variation of 7, 14, 21, 28, 35 days. While the pressure used 75 Kg/cm2, so it is necessary to study based on variations of pressure to get the optimum condition of the paving blocks. Form of test specimens by SNI 03-0691-1996 with paving block size of 20 cm x 10 cm x 6 cm.The test results showed The addition of 5 wt.% Fa increases the compressive strength when compared to 0 wt.% Fa. Optimal compressive strength occurred in paving block compacting pressure 95 kg/cm2 in the amount of 36.1 kg/cm2 with a quality that is used for road on the composition 5 wt.% Fa and 0 wt.% Fa of 30.3 kg/cm2 with quality B parking area. This is because the material fly ash contains oxide compounds that have mechanical properties that are very good and and the size of the fly ash used is very small so as to fill the voids between particles and reduce the porosity of the paving blocks and the higher pressure causes the density of paving blocks increases because bond between the particles is getting stronger. All the results that have made the products meet the quality according to SNI 03-0691-1996.